Sustainable Green Supply Chain Management and Waste Management in Construction Industry - KUMAR, DR.D. BARANI; BIKILA, MR. MESFIN LEGESE; CHALA, MR. GUDETA (The journal of contemporary issues in business and government, 2021)
The contemporary trends of Green supply chain management (GSCM) are creating awareness within construction industries rapidly. It is functioning as a catalyst to realize competitive advantage and sustainability, environment consciousness and globalizing. Environmental pollution and global climate change have turned out to be one of the greatest challenges which have constrained governments and businesses alike to assess the environmental impacts of their activities. The green construction sector has therefore turn out to be critically important. Green supply chain management is taken into account as an environmental innovation in construction industry. At present scenario the environmental issues and the concern for sustainability is encouraging more effective usage of energy, water and material currently used, ensure the prevention of any kind of waste, perform environmentally sensible and eco-friendly building design and be environmentally friendly in the process of the construction. Industries are aware of their responsibilities about the environment depending on regulations. This leads to sustainable systems that will continue their processes without giving any harm to the environment. Environmental issues are seen at every step of supply chain that starts from getting the raw material and ends with reuse or recycle or disposal. Sustainability is very important to improve the quality of systems to have a healthy environment with high level of social, economic and environmental conditions to future generations. It identifies linkages between research and practice in the area of reverse supply chain and how it can facilitate the management of waste. The entire stream of research on reverse supply chains is motivated by the observations that by reusing, remanufacturing, and recycling used products/components it is possible to reduce landfill waste. This article is the benchmark of further research to find out the relationship between GSCM practices and construction industry for improving sustainability.